Prey defence phenotype mediates multiple‐predator effects in tri‐trophic food webs. Issue 10 (30th July 2022) - Guariento, Rafael Dettogni; Dalponti, Guilherme; Carneiro, Luciana Silva; Caliman, Adriano
Abstract: The emphasis on mechanisms governing the interaction among predators (e.g. cooperation, competition or intraguild predation) has driven the understanding of multiple‐predator effects on prey survival and dynamics. However, overwhelming evidence shows that prey can adaptively respond to predators, exhibiting multiple defensive phenotypes to cope with predation. Nevertheless, there is still a relatively scarce theory connecting the emergence of prey defences in complex multi‐predator scenarios and their ecological consequences. Using a mathematical approach, we evaluated the prevalence of defended prey phenotypes as a function of predator‐induced mortality in a two‐predator system, and how prey and phenotype dynamics affect trophic cascades. We also evaluated such responses when prey manifests a general defence against both predators (i.e. risk reducing) or a specialized defence against one predator at the expense of defence against the other predator (i.e. risk trade‐off), and when such phenotypes induce fitness and foraging costs. We showed that the emergence of defended phenotypes under multiple predators depends on predator‐induced mortality rates, the magnitude of phenotype costs and the effect of the defensive phenotype on the performance of all predators. Risk‐reducing phenotypes enhance prioritized responses to predators with high killing rates, but prioritized responses are diminished when prey manifest risk trade‐off phenotypes. Finally, we showed that resource abundance across the predation gradient directly depends on the prevalence of certain prey phenotypes and their effect on foraging costs. Ultimately, our results depict the implications of prey defences on prey and basal resources abundance in a multiple predators' environment, highlighting the role of the identity of defensive strategies in mediating the strength and nature of trophic cascades, via consumptive or non‐consumptive effects. Abstract : The likelihood of prey to manifest defensive traits in multi‐predator communities depends on three features: predator killing rates, the costs of carrying a defence and how these defences affect other predator's ability to kill prey, ultimately affecting how predators influence the strength and nature of trophic cascades. Resumo: A ênfase nos mecanismos que governam a interação entre predadores (por exemplo, cooperação, competição ou predação intra‐guilda) tem impulsionado a compreensão dos efeitos de múltiplos predadores na sobrevivência e dinâmica de presas. No entanto, fortes evidências mostram que as presas podem responder de forma adaptativa aos predadores, exibindo vários fenótipos de defesa para lidar com a predação. No entanto, ainda há uma teoria relativamente escassa conectando a manifestação de defesas em presas em cenários com múltiplos predadores e suas consequências ecológicas. Usando uma abordagem matemática, avaliamos a prevalência de fenótipos de defesa de presas em função da mortalidade induzida por predadores em um sistema de dois predadores, e como a dinâmica de presas e dos fenótipos afeta a cascata trófica. Também avaliamos tais respostas quando a presa manifesta uma defesa geral contra ambos os predadores (ou seja, redução de risco) ou uma defesa especializada contra um predador em detrimento da defesa contra o outro predador (ou seja, trade‐off de risco), e quando tais fenótipos induzem custos ao fitness e ao forrageamento. Nós mostramos que a manifestação de fenótipos de defesa sob múltiplos predadores depende das taxas de mortalidade induzidas pelo predador, da magnitude dos custos do fenótipo e do efeito do fenótipo no desempenho dos predadores. Os fenótipos de redução de risco aumentam as respostas priorizadas aos predadores com altas taxas de predação, mas as respostas priorizadas são reduzidas quando as presas manifestam fenótipos de trade‐off de risco. Finalmente, mostramos que a abundância de recursos ao longo do gradiente de predação depende diretamente da prevalência de determinados fenótipos e seus efeitos no forrageamento da presa. Em última análise, nossos resultados retratam as implicações das defesas contra predadores na abundância de presas e recursos basais em um ambiente com múltiplos predadores, destacando o papel da identidade de estratégias de defesa na mediação da força e natureza das cascatas tróficas, via efeitos de consumo ou comportamentais.